KONTRIBUSI INFLUENCER PADA PURCHASE INTENTION DENGAN SIKAP TERHADAP INFLUENCER SEBAGAI VARIABEL MEDIASI - Faadiyah Nisa; Robert Kristaung (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
This study was conducted to analyze the effect of influencers' contributions on purchase intention with attitudes toward influencers as a mediating variable in the investment industry in Indonesia. This study used a questionnaire from 200 respondents distributed using purposive sampling technique. Hypothesis analysis was carried out using the partial least squares (PLS) test, which is one of the structural equation modeling (SEM) approaches. The results showed that the contribution of influencers consisting of perceived credibility, trust, perceived behavioral control, subjective norms, and perceived expertise had a positive effect on attitudes towards influencers. However, perceived congruence does not have a positive effect on attitudes towards influencers. In addition, attitudes towards influencers have a positive effect on purchase intention.